Grid and distributed computing International Conference, GDC 2011, Held as Part of the Future Generation Information Technology Conference, FGIT 2011, Jeju Island, Korea, December 8-10, 2011. Proceedings - GDC 2011 (2011 Cheju Island, Korea); Kim, Tai-hoon.; Adeli, Hojjat; Cho, Hyun-seob.; Gervasi, Osvaldo; Yau, Stephen S.; Kang, Byeong-Ho.; Villalba, Javier García; SpringerLink (Online service). (Berlin Heidelberg Springer, 2011)
This book constitutes the refereed proceedings of the International Conference, GDC 2011, held as Part of the Future Generation Information Technology Conference, FGIT 2011, Jeju Island, Korea, in December 2011. The papers presented were carefully reviewed and selected from numerous submissions and focuse on the various aspects of grid and distributed computing.
Electronic reproduction.
Keywords: Computational grids (Computer systems) -- Congresses; Electronic data processing -- Distributed processing -- Congresses; Electronic books